2011
DOI: 10.1007/s00018-011-0639-0
|View full text |Cite
|
Sign up to set email alerts
|

The sheddase activity of ADAM17/TACE is regulated by the tetraspanin CD9

Abstract: ADAM17/TACE is a metalloproteinase responsible for the shedding of the proinflammatory cytokine TNF-α and many other cell surface proteins involved in development, cell adhesion, migration, differentiation, and proliferation. Despite the important biological function of ADAM17, the mechanisms of regulation of its metalloproteinase activity remain largely unknown. We report here that the tetraspanin CD9 and ADAM17 partially co-localize on the surface of endothelial and monocytic cells. In situ proximity ligatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 51 publications
3
80
1
Order By: Relevance
“…Interestingly, although the cytoplasmic tail of ALCAM contains clusters of positively charged amino acid residues that typically interact with members of the ezrin/radixin/moesin (ERM) family, a study performed with pulmonary microvascular ECs found no association between ALCAM and ERM protein family members, corroborating our results (53). Furthermore, Gilsanz et al (54) have recently reported that ALCAM forms a complex with the tetraspanin molecule CD9 and the "sheddase" ADAM17, which together regulate ALCAM expression and activity (55). Although CD9 is highly expressed on ECs (56), we were unable to confirm the link between ALCAM and CD9.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, although the cytoplasmic tail of ALCAM contains clusters of positively charged amino acid residues that typically interact with members of the ezrin/radixin/moesin (ERM) family, a study performed with pulmonary microvascular ECs found no association between ALCAM and ERM protein family members, corroborating our results (53). Furthermore, Gilsanz et al (54) have recently reported that ALCAM forms a complex with the tetraspanin molecule CD9 and the "sheddase" ADAM17, which together regulate ALCAM expression and activity (55). Although CD9 is highly expressed on ECs (56), we were unable to confirm the link between ALCAM and CD9.…”
Section: Discussionsupporting
confidence: 89%
“…ADAM17 has been shown to interact with the tetraspanin CD9 on leukocyte and endothelial cell membranes to regulate ADAM17 cleavage of TNF-a and ICAM-1, as well as with protein disulfide isomerase in cleavage of the same substrates. 39,40 The potential role of any molecules interacting with ADAM17 during Notch cleavage is unknown. Although homologs of ADAMs 10 and 17 are functionally redundant in C. elegans, 23 it is unknown if ADAM17 has a normal in vivo role in Notch cleavage in higher animals.…”
Section: Do Not Distributementioning
confidence: 99%
“…The functional relevance of the interaction between the c-secretase complex and proteins from the tetraspanin-enriched microdomains was also demonstrated using cells derived from CD81-and CD9-knockout mice where the c-secretase activity was significantly impaired. For some cellular processes, treatment with monoclonal antibodies against tetraspanin molecules has been shown to have either an agonist or antagonist activity [22,24,53]. In this study, c-secretase activity was also a target for modulation using antibodies against the CD81 and CD9 tetraspanins, which resulted in a disruption, more evident for CD9, of the Ab generation, thus implicating TEMs in the endogenous regulation of c-secretase [52].…”
Section: Tetraspanins and C-secretasesmentioning
confidence: 85%
“…MT1-MMP subcellular localization is also dependant on its association with CD44, which is in turn shedded by the protease, and is also a component of TEMs Functional interplay between tetraspanins and proteases 3329 ADAM17 [92,93], and elevated soluble levels of these proteins have been found in several inflammatory and tumoral pathologies [94,95]. Hence, CD9 silencing on stimulated HUVEC results in a marked decrease in the membrane level of ICAM-1 reflecting the release from the inhibitory effect exerted by CD9 on ADAM17 activity [24]. These results also provide a mechanism by which CD9 regulates the levels of ICAM-1 on endothelial cells and reinforces the subsequent consequences in terms of leukocyte adhesion and transmigration [91,96].…”
Section: Regulation Of Proteolysis At the Substrate Levelmentioning
confidence: 99%
See 1 more Smart Citation